Indoleamine 2,3-Dioxygenase Immune Status as a Potential Biomarker of Radioiodine Efficacy for Advanced Distant Metastatic Differentiated Thyroid Cancer - Shi, Liang; Duan, Rui; Jia, Qiong; Wu, Wenyu; Zhou, Jianming; Li, Shaohua; Zhang, Hao; Xue, Xue (Frontiers in Oncology, 2022)
Purpose: Host immunity influences the impact of cancer therapy but the effect of immune status in radioiodine (RAI)-treated differentiated thyroid cancer (DTC) remains obscure. Here we investigated indoleamine 2,3-dioxygenase (IDO)-mediated immune activity as a biomarker of response to RAI in patients with distant metastatic DTC (dmDTC). Methods: Patients with dmDTC receiving RAI were evaluated for serum IDO activity (kynurenine and kynurenine:tryptophan ratio) at baseline and 3 months after RAI. The most accurate cut-off for these biomarkers to predict response was established by receiver operating characteristic analysis. The relationship between disease outcomes, overall survival (OS) and progression-free survival (PFS), and IDO activity levels was studied. Results: Higher baseline kynurenine:tryptophan ratio (>2.46) identified nonresponders with shorter median PFS (45 mo versus not reached, P=0.004) and OS (78 mo versus not reached, P=0.041). Higher post/pre-kynurenine ratio (>1.69) was also associated with with survival endpoints: shorter median PFS 48 mo versus not reached, P=0.010) and OS (68 mo versus not reached, P=0.002). Favorable baseline and favorable change corresponded with better PFS and OS (neither reached after 64 months median follow-up). Conclusions: Our results suggest that RAI alters IDO-mediated immune activity in dmDTC patients. Elevated IDO activity predicts poor survival outcomes for advanced dmDTC patients and lower likelihood of response to RAI. Further study is needed to confirm our results in a larger sample, and to investigate the effect of immunotherapy targeting IDO, which might contribute to optimization of RAI treatment for advanced dmDTC patients.